Physical Activity and Stress Levels on the Eating Behavior of Elementary School Amid the Covid-19 Pandemic - Ayu Mutiara Santanu; Syifa Fakhomah Syihab; Muchamad Rizki Sentani; Hurry Mega Insani (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
The objective of this study is to analyze the relationship between physical activity and stress levels on the eating behavior of elementary school-aged children amid the Covid-19 pandemic in Garuda Village, Bandung, West Java. A cross-sectional research design was used in this study. We recruited 173 elementary school children in Garuda Village, Bandung, West Java. Research data were collected by questionnaire. Study measures included a general information survey, anthropometric measurements, a Perceived Stress Scale (PSS), an International Physical Activity Questionnaire (IPAQ), and Food Frequency Questionnaire (FFQ). Univariate, bivariate, and multivariate analyses were used. The result showed children’s nutrition intake is associated with the education of fathers and mothers. Students with mild stress levels showed a good eating pattern (55.8%) and students with moderate stress levels had a poor diet (54.2%). There was a relationship between physical activity and the diet of elementary school students (p-value = 0.049) (p 0.05) and students with sedentary physical activity have an opportunity of 2.289 times to have an adequate diet. Gender, father’s education, mother’s education, father’s occupation, mother’s occupation, income, and perception of stress were not related to the student’s diet (p-value 0.05).